Perencanaan Penatagunaan Lahan Pasca Tambang Timah - Eddy Ibrahim; Hartini Iskandar; Ulma Aydilla (Seminar Nasional Lahan Suboptimal, 2019)
Ibrahim E, Iskandar H, Aydilla U. 2019.  Planning for land management of post tin mine. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 157-162. Palembang: Unsri Press. PT Timah Tbk, tin producer located in Bangka Belitung Island. The study was conducted on a former mining area x which has a total area of 28.77 ha. The location was in the form of tailings and high mounds along the pit. Therefore, it is necessary to arrange the surface of the land to become a ready land for reclamation, and it is expected to become more productive land. The purpose of this study is to calculate the amount of overburden material used for land management of post tin mining and the calculation of the time required. From the calculation results obtained the volume of overburden available in x mining land amounted to 78.049,4 m3, while the total volume of mine holes was 146.258,83 m3, so the effort made based on the calculation analysis was not all under will be stockpiled due to limitations of overburden. The time required for this ground leveling activity was 1 month by using 1 unit of bulldozer.Keywords: overburden, pit, reclamation, top soil